SYRINGE FEEDING VERSUS BOTTLE FEEDING; IMPACT ON BREAST FEEDING: Feeding Methods For Neonates - Aatif, Dr Muhammad; Jalil, Jawad; Basheer, Faisal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the effects of syringe feeding versus bottle feeding on subsequent breast feeding in term infants admitted to the nursery for routine care for the first 12–24 hours of life. Study Design: Prospective cohort study. Place and Duration of Study: Nurseries of Combined Military Hospital Gujranwala and Mangla, from Feb 2016 to Jul 2016. Patients and Methods: All term neonates fulfilling inclusion criteria were included in the study. All neonates admitted for observation delivered by lower segment caesarean section to the nursery at CMH Gujranwala were placed in group 1. They were initially syringe fed while being observed in nursery (12-24 hours) and subsequently advised to start breast feeding. Whereas all neonates admitted for observation to the nursery at CMH Mangla were placed in group 2. They were initially bottle fed and subsequently advised to breast feed. All infants were followed up at 1.5 months to determine feeding practices. At follow-up, infants were categorised as either exclusively breast fed or not exclusively breast fed. Results: In group 1, 62.2% of infants were exclusively breast feeding at 1.5 months. In group 2, 59% of infants were exclusively breast feeding at 1.5 months. Group 1 did not have a significantly higher number of infants who were exclusively breastfed as compared to group 2 (p-value 0.64). Conclusion: Supplementary feeding with syringe feeding as compared to bottle feeding does not confer any benefit in establishing exclusive breastfeeding in healthy term infants who are unable to breast feed for initial 12- 24 hours and hence cannot be recommendedas the preferred method of supplementary feeding in this group of neonates.